Population density and primate conservation in the Noroeste Biosphere Reserve, Tumbes, Peru - Cindy M. Hurtado; José Serrano-Villavicencio; Víctor Pacheco (Revista Peruana de Biología, 2016)
The Noroeste Biosphere Reserve (NBR) is home to at least 22 species of medium and large mammals including the primates Alouatta palliata aequatorialis and Cebus albifrons aequatorialis. Previous estimates of A. p. aequatorialis population density vary from 2.3–8.6 ind/km2 in 1983 to 17–19 ind/km2 in 2005 and 2006, respectively. While for C. a. aequatorialis there are no estimates of population density in the NBR. In order to calculate the population density estimates for both species we installed six transects in 10.5 km2 within the Cerros de Amotape National Park (belonging to the NBR) from August 2012 to March 2013. Based on 112.3 km of transects we obtained a population density of 8.3 ± 3.6 ind/km2 for A. p. aequatorialis. However, for the reduced number of Cebus albifrons aequatorialis sightings we were only able to calculate a group size from three to 12 individuals and an encounter rate of 0.3 ind/km. Even though A. p. aequatorialis has potentially increased in population density, it is not feasible to make comparisons with previous estimates in the same area because of the different employed methodologies and the lack of randomness in the data collection. We recommend a long-term monitoring plan, including C. a. aequatorialis which makes it a conservation priority for the NBR, this monitoring plan should include mitigation of potential threats such as illegal hunting and trapping for the pet trade.